Brain lesion in a recreational drug user: Isolated cerebral mucormycosis. (2020) - Ha, Ngoc-Tram; Lowery, Megan; Woo, Jean; Mehta, Yatin; Bhanot, Nitin
Abstract: Isolated cerebral mucormycosis is a relatively rare and unique variant of mucormycosis which is seen most commonly in patients with intravenous recreational drug use. While this invasive fungal infection in the brain is thought to spread from the sinuses or the lungs in other hosts such as diabetics and those with malignancy, hematogenous spread and seeding has been attributed in the pathogenesis of isolated cerebral mucormycosis. Clinical features and radiological findings may be non-specific and hence, heightened clinical suspicion for a prompt diagnosis and early medical and surgical intervention is paramount for a favorable outcome in such rare, but potentially fatal infections.